2003
DOI: 10.1038/sj.sc.3101440
|View full text |Cite
|
Sign up to set email alerts
|

Dysphagia in patients with acute cervical spinal cord injury

Abstract: Study design: Longitudinal observational. Objectives: (a) To establish a reliable and feasible method to indicate the presence and severity of dysphagia and (b) to establish a course of treatment in individuals presenting with cervical spinal cord injury (CSCI). Setting: Spinal Cord Injury Center, Werner Wicker Klinik, Bad Wildungen, Germany. Patients and methods: This is a cross-sectional study of 51 patients consecutively admitted to the Intensive Care Unit of the SCI in-patient service. They were subjected … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
76
0
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(81 citation statements)
references
References 20 publications
4
76
0
1
Order By: Relevance
“…Age was found to be statistically related to dysphagia by Kirshblum et al, 7 but not by Wolf and Meiners, 2 Abel et al 8 or Seidl et al 9 In the present study, the mean age of patients with aspiration was significantly higher compared with the patients without evidence of aspiration. Even linear by linear association after categorization in different age groups showed higher prevalence of dysphagia with increasing age.…”
Section: Discussionsupporting
confidence: 57%
See 2 more Smart Citations
“…Age was found to be statistically related to dysphagia by Kirshblum et al, 7 but not by Wolf and Meiners, 2 Abel et al 8 or Seidl et al 9 In the present study, the mean age of patients with aspiration was significantly higher compared with the patients without evidence of aspiration. Even linear by linear association after categorization in different age groups showed higher prevalence of dysphagia with increasing age.…”
Section: Discussionsupporting
confidence: 57%
“…This correlation was also supported in previous studies. 2,[7][8][9] Although the cause-effect relationship between dysphagia and the need for tracheostomy is unclear, various reports of increased risk of dysphagia through tracheostomy give weight to the possibility that risk of dysphagia increases through the existence of tracheostomy in cervical spinal cord injury patients. This was also evident in the present study, as the incidence of aspiration was significantly related to the presence of tracheostomy by the time of VFSS, but not to the history of tracheostomy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As mechanical alteration of the tissues during an anterior approach has repeatedly been described as the mechanism for dysphagia, a different treatment of the tissues must be the reason for the improved results in our population. Problems during the surgical procedure must be considered in Wolf's study, 5 in which the cause of dysphagia was, in all cases, identified as laryngeal swelling. Such swelling generally arises due to a lack of lymphatic or other drainage as a result of trauma.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3] The most recent estimate of dysphagia incidence within one month is 40%. 4 The detrimental consequences of dysphagia in SCI include primarily pulmonary with transient hypoxemia, chemical pneumonitis, mechanical obstruction, atelectasis, bronchospasm, and pneumonia.…”
mentioning
confidence: 99%